The case for therapeutic proteostasis modulators - Vij, Neeraj (2011)
A functional ubiquitin proteasome pathway (UPP) is vital for all eukaryotic cellular systems and therefore any alteration in this critical component of proteostasis machinery has rpotential pathological consequences. A proteostasis imbalance can be induced by environmental pollutants, age or genetic factors. Though the exact underlying mechanisms are unclear, a decrease in proteasome activity weakens the homeostatic cellular capacity to remove proteins that are either misfolded or need to be replenished, which favors the development of neurodegenerative, cardiac and other conformational diseases. In contrast, induction of proteasome activity is an attribute of many diseases including muscle wasting, sepsis, cachexia and uraemia. In the case of misfolded protein disorders, higher degradation of a single protein leads to the pathophysiological consequences due to the absence of functional protein. Therefore, selective proteostasis inhibition is a potential treatment strategy for misfolded protein disorders, while broad-spectrum proteasome inhibitor drugs are designed to target tumor metastasis. In contrast, for muscle wasting and neurodegeneration, the use of proteostasis-activating or modulating compounds could be more effective.